Ethicalness in Educational Research Training - Arturo Cristóbal Álvarez Balandra; Virginia Álvarez Tenorio (Universidad Autónoma de Madrid, 2016)
The training of researchers is currently an imperative for universities to fulfill its historic role of generating knowledge in diverse fields of science, technique and technology and accordingly benefit humanity and foresee its welfare. Purpose that many institutions successfully achieve, creating an impact on the final efficiency and consolidation of specialized academic blocks; however, it is in these processes of training where most cases left aside the ethical reflection on the implications that the investigative work has. Dimension that results relevant as it is the scientific scope of the specialty, to proceed critically, dialogically and ethically with the surroundings and the involved subjects.